Physically cross-linked PVA-quaternized chitosan-Ag NPs composite hydrogel membranes for potential topical wound healing applications: Synthesis, physicochemical properties, and in vitro bioevaluation - El-Refaie S. Kenawy, Elbadawy A. Kamoun, Samia M. Elsigeny, Samira Haikal, Ashraf A. El-Shehawy, Yehia A. G. Mahmoud (Journal of Applied Pharmaceutical Science, 2023)
Physically cross-linked composite hydrogel membranes composed of different ratios of polyvinyl alcohol- (PVA-) grafted modified chitosan (Cs) with glycidyltrimethylammonium chloride (GTMAC) loaded with Ag nanoparticles as an active ingredient were synthesized by the freezing-thawing (F-T) cycle technique. F-T cycles were conducted repetitively three times to guarantee PVA-Cs chains entanglement occurring. The reactants, membrane composition, and cross-linking process were verified and characterized by several instrumental analyses. The physicochemical properties of the PVA-Cs-g-GTMAC hydrogel membrane, such as swelling ratio, mechanical properties, gel fraction % (GF %), hydrolytic degradation, and thermal stability, were discussed in detail. The results revealed that, with increasing of the Cs-g-GTMAC content in the hydrogel membranes, the swelling ratio, mechanical properties, and hydrolytic degradation of the cross-linked membranes increased clearly; however, GF % decreased progressively. Furthermore, in order to assess in vitro bioevaluation of the tested composite membranes, e.g., cytotoxicity and antimicrobial studies against the HFB-4 cell line and both Staphylococcus aureus and Escherichia coli, respectively, were assessed using the MTT assay and disc diffusion method, respectively. Notably, all tested composed hydrogels exhibited high cell viability % after different incubation times and varied hydrogel concentrations. The findings referred to the idea that prepared hydrogel membranes could be professionally employed as antibacterial biomaterials/ dressings for wound healing purposes.
Keywords: PVA-quaternized chitosan, Ag NPs, freezing-thawing cycle, hydrogel membranes